Land, Mobility, and Belonging in West Africa : Natives and Strangers - Lentz, Carola (Book collections on Project MUSE., 2013)
Focusing on an area of the savannah in northern Ghana and southwestern Burkina Faso, this book explores how rural populations have secured, contested, and negotiated access to land and how they have organized their communities despite being constantly on the move as farmers or migrant laborers. The author seeks to understand how those who claim native status hold sway over others who are perceived to have come later. As conflicts over land, agriculture, and labor have multiplied in Africa, this book shows how politics and power play decisive roles in determining access to scarce resources and in changing notions of who belongs and who is a stranger.